INTERDISCIPLINARITY: AN ATTITUDE, A NEW LOOK, A SEARCH FOR THE LOST UNITY OF KNOWLEDGE - Araújo da Costa, Marluce; Cristina Medeiros de Azevedo Silva, Ana; de Cáscia da Costa, Francisca; Amilton da Costa, José; Medeiros, Salésia (Revista Gênero e Interdisciplinaridade, 2025)
This article theoretically addresses interdisciplinarity, highlighting the existence of various interpretations of this topic in education. Initially, we seek to define the term and its context, its etymology, the different types of relationships, the assumptions, and their implications for teaching practice. We then discuss its limits and possibilities, bottlenecks, and the basic aspects of interdisciplinary practice.